PERSPECTIVES FROM THE FIELD: Opinion: The NEPA and Major Water Resource Planning for the Future. What's the problem? Analysis Paralysis. (24th February 2016) - Francis, Michael
Abstract : Federal water resources development planning and the associated environmental assessment processes have been very complex and expensive. Federal water resource agencies are reassessing approaches to planning, with the support of our leadership and legislators, which encourages National Environmental Policy Act (NEPA) practitioners to apply the Council on Environmental Quality guidance to improve NEPA and to work with regulating agencies to streamline efforts and provide reasonable levels of information adequate for risk informed decision making. Environmental Practice 18: 69–71 (2016)